INCREASING QUALITY OF PROCES EDUCATION WITH CA- SYSTEMS APPLICATION - JURKO, Jozef (Trends in education, 2008)
The paper described research a new trends in proces education by technical discipline. Application of CA-systems is very important for practice and a quality of proces education. The paper is part of result from solution of Project VEGA 1/3173/06.
Keywords: cutting; simulation; technological process